Torque change of anterior teeth based on CBCT using a universal table - I. S. Kopetskiy; N. G. Meskhiya; A. I. Kopetskaya; I. A. Nikolskaya; G. S. Kabisova (Эндодонтия Today, 2022)
Aim. The thickness of bone tissue in patients with pathological dental inclinations planning orthodontic treatment with fixed equipment.Materials and methods. The CBCT scans of patients with pathological dental inclinations was studied, bone tissue deficiency was described, a universal table was given that helps to calculate the necessary thickness of bone tissue at various levels of root length at the stage of treatment planning when the torc of the frontal teeth changes.Results. Bone tissue deficiency is described in two study groups, however, in patients with retrusion, the deficiency is most pronounced in the cervical third from the vestibular side, in the group with protrusion, the deficiency is described in the cervical third from the oral surface in the cervical third.Conclusions. The article describes a clinical case of orthodontic treatment using a universal table. The principle of operation of the universal table is shown, as well as its own clinical results proving the effectiveness of the universal table are described.